2015
DOI: 10.1177/2322093715576161
|View full text |Cite
|
Sign up to set email alerts
|

What Happens to Female Employees in Skewed IT Project Teams in Sri Lanka? Revisiting Kanter

Abstract: Post-war Sri Lanka is heavily dependent on the promising future of the Information Technology (IT) industry to contribute considerably to the economic and social development of the country. Given the reported skill shortage and gender imbalance in the IT sector, female participation and retention is greatly advocated and promoted. In this milieu, we aim to understand what happens to female employees in male-dominant IT project teams, and the challenges and issues they face, as well as the related causes, using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 40 publications
2
10
0
Order By: Relevance
“…But, intercultural competencies are seen as very important in tasks with high levels of communications [SLR(Holtkamp et al 2015 )], and (3) some cultures can lead to strong stereotypical beliefs that challenge women in teams dominated by men. These women have perceived difficulties having their work recognized, proving themselves, and feeling members of their team [SLR(Adikaram and Wijayawardena 2015 )].…”
Section: Resultsmentioning
confidence: 99%
“…But, intercultural competencies are seen as very important in tasks with high levels of communications [SLR(Holtkamp et al 2015 )], and (3) some cultures can lead to strong stereotypical beliefs that challenge women in teams dominated by men. These women have perceived difficulties having their work recognized, proving themselves, and feeling members of their team [SLR(Adikaram and Wijayawardena 2015 )].…”
Section: Resultsmentioning
confidence: 99%
“…A third theme found in the articles referencing Ahuja () has to do with the IT work environment and perceptions of exclusion (Adikaram & Wijayawardena, ; Wentling & Thomas, ) and the negative influence of this exclusion on women's career opportunities (eg, Orser, Riding, & Stanley, ; Raghuram, ). For example, Adikaram and Wijayawardena () found that women in Sri Lanka working on project teams containing primarily men were treated as “outsiders” and constantly had to prove themselves to their colleagues. This undermined the women's ability to advance within the organization.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They are generally exposed to different cultures, maintain a sound command of English language and are exposed to people coming from different backgrounds (Fernando and Cohen, 2013). Even with that exposure, “gendered” work norms bring difficulties and hardships for the few women engineers employed in the IT sector in Sri Lanka (Adikaram and Wijayawardena, 2015). For instance, there is an increasing trend of teamwork within IT firms (Perera and Fonseka, 2011; Jayawarna and Fonseka, 2011) in the form of multi-functional and multi-skilled project teams, which require the few women employed there to be interconnected with their male team members (Adikaram and Wijayawardena, 2015).…”
Section: It Industry As Highly Genderedmentioning
confidence: 99%
“…Even with that exposure, “gendered” work norms bring difficulties and hardships for the few women engineers employed in the IT sector in Sri Lanka (Adikaram and Wijayawardena, 2015). For instance, there is an increasing trend of teamwork within IT firms (Perera and Fonseka, 2011; Jayawarna and Fonseka, 2011) in the form of multi-functional and multi-skilled project teams, which require the few women employed there to be interconnected with their male team members (Adikaram and Wijayawardena, 2015). The expectation in the industry is that everybody will perform equally, regardless of gender, if they have similar levels of skills and qualifications.…”
Section: It Industry As Highly Genderedmentioning
confidence: 99%
See 1 more Smart Citation